The Innovation Revolution in Agriculture. A Roadmap to Value Creation - Campos, Hugo (Springer, 2021)
This open access book is an important reframing of the role of innovation in agriculture. Dr. Campos and his distinguished coauthors address the need for agriculture to feed a growing global population with a reduced environmental footprint while adapting to and mitigating the effects of changing climate. The authors expand the customary discussion of innovation in terms of supply driven R&D to focus on the returns to investors and most importantly, the value to end-users. This is brought to life by exploring effective business models and many cases from agricultural systems across the globe. The focus on converting the results of innovation in R&D into adoption by farmers and other end-users is its greatest contribution. Many lessons from the book can be applied to private and public sectors across an array of agricultural systems. This book will be of enormous value to agri-business professionals, NGO leaders, agricultural and development researchers and those funding innovation and agriculture across the private and public sectors.